Respuesta :

Answer:

log 64

Step-by-step explanation:

Using the rules of logarithms

• log [tex]x^{n}[/tex] ⇔ nlogx

• logx + logy ⇔ log xy

Given

2 log 4 + log 2 + log 2

= log 4² + log (2 × 2)

= log 16 + log 4

= log (16 × 4) = log 64

 

Answer:

A, log 64

Step-by-step explanation:

your answer A, log 64 is correct. i will explain why below:

2 log 4, log 2 and log 2 have the same bases (10), meaning they are able to be added easier. but before we add, we use the Power Rule of Logarithms on 2 log 4

the Power Rule says that we can move an exponent in a logarithm to the front then solve. this also applies to the reverse, as we can move 2 back as an exponent of 4 and solve

2 log 4 ---> log 4² < simplify the exponent and we get log 16

we can now use the Product Rule of Logarithms where log x + log y = log(xy)

we can use that on the first two terms of the addition

log 16 + log 2 ----> log (16 × 2) = log 32

now we can apply the other log 2 to the rule but instead with log 32

log 32 + log 2 ---> log (32 × 2) = log 64

our answer is log 64